Advanced Glycation End Product Accumulation in Subjects with Open-Angle Glaucoma with and without Exfoliation - Shirakami, Tomoki (Antioxidants (Basel), 2020)
Advanced glycation end products (AGEs), which are the products of a non-enzymatic reaction between reducing sugars and other macromolecules, are critical in aging, as well as metabolic and degenerative diseases. To assess the involvement of AGEs in glaucoma, skin autofluorescence (sAF) level, which is a measurement of AGEs’ accumulation, was compared among Japanese patients with glaucoma (316 with primary open-angle glaucoma (PG) and 127 exfoliation syndrome and glaucoma (EG)) and controls (133 nonglaucomatous controls) (mean age 71.6 ± 12.8 years, 254 men and 322 women). The sAF values were estimated from the middle fingertip using a 365 nm light-emitting diode for excitation and detection at 440 nm emission light. The estimated AGE values (arbitrary unit) were 0.56 ± 0.15, 0.56 ± 0.11, and 0.61 ± 0.11 in the control, PG, and EG groups, respectively (p < 0.0001, analysis of variance); and were significantly higher in the EG group than the control (p = 0.0007) and PG (p < 0.0001) groups. After adjustment for various demographic parameters by multivariate analyses, male sex (standard β = 0.23), EG (0.19), and diabetes (0.09) were associated with higher AGE levels; PG (−0.18) and smoking (−0.19) were associated with lower AGE levels. Age, visual acuity, intraocular pressure, glaucoma medications, lens status, and systemic hypertension were not associated with AGEs. The high AGE level in EG suggested that specific oxidation and glycation mechanisms underlie the glaucoma pathogenesis associated with pseudoexfoliation syndrome.